2021
DOI: 10.1186/s12944-021-01512-x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in complex lipids in tumor tissue of patients with colorectal cancer

Abstract: Background Accumulating evidence indicates alterations in lipid metabolism and lipid composition in neoplastic tissue. Earlier nuclear magnetic resonance studies showed that the contents of major lipid groups, such as triacylglycerols, phospholipids and cholesterol, are changed in colon cancer tissue. Methods In this study, a more detailed analysis of lipids in cancer and tumor adjacent tissues from colorectal cancer patients, using liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…The alkyl-lysophospholipid analogue edelfosine, resveratrol, miltefosine, and inhibitors of SM metabolism enzymes were used to alter tumor cell membrane fluidity and permeability and showed remarkable efficacy in preventing tumor progression [ 54 , 85 , 103 , 104 ]. Devising novel anticancer strategies based on the modulation of lipid metabolism and the composition of the cell membrane was recently advised for the treatment of cancer and overcoming drug resistance, pioneering a novel field named membrane-lipid therapy [ 104 106 ]. Combination of chemotherapeutic drugs and Cer is presently increasingly used for tumor treatment [ 47 , 51 , 107 109 ].…”
Section: Manipulating Sphingomyelin Metabolism For Cancer Controlmentioning
confidence: 99%
“…The alkyl-lysophospholipid analogue edelfosine, resveratrol, miltefosine, and inhibitors of SM metabolism enzymes were used to alter tumor cell membrane fluidity and permeability and showed remarkable efficacy in preventing tumor progression [ 54 , 85 , 103 , 104 ]. Devising novel anticancer strategies based on the modulation of lipid metabolism and the composition of the cell membrane was recently advised for the treatment of cancer and overcoming drug resistance, pioneering a novel field named membrane-lipid therapy [ 104 106 ]. Combination of chemotherapeutic drugs and Cer is presently increasingly used for tumor treatment [ 47 , 51 , 107 109 ].…”
Section: Manipulating Sphingomyelin Metabolism For Cancer Controlmentioning
confidence: 99%
“…This study further reported TG signatures as a potential discriminant in differentiating tumour from non-cancerous tissue. Conversely to the accumulation of LDs, other recent studies have reported decreased TG levels in patient-derived CRC tissues compared to normal mucosa [ 39 , 55 ]. Mika et al reported reduced levels of TG in a study of 25 CRC tissue and patient-matched controls using 1 H-nuclear magnetic resonance ( 1 H-NMR) methods [ 55 ], while Pakiet et al observed decreases in 21 TG, 8 DG, and one MG lipid species and decreased overall TG content in an LC-MS study of 10 patient-derived CRC tissues compared to normal mucosa [ 39 ].…”
Section: The Role Of Lipids In Crcmentioning
confidence: 99%
“…Relative reduction of PUFA and increased SFA over UFA incorporation are thought to protect from lipid peroxidation-mediated cell death and metabolic stress, by neutralizing reactive oxygen species (ROS) and thus increasing cell survival, tumor progression and metastasis [ 19 , 38 , 39 ]. De novo fatty acid synthesis in CRC was shown to increase lipid raft formation within cellular membranes and thereby modulate accessibility for signal transduction proteins and additionally, tumor tissues showed distinct enriched profiles of highly complex lipid species [ 38 , 40 , 41 , 42 ].…”
Section: Lipid Biology In Crcmentioning
confidence: 99%
“…Somatic cells compared to tumor cells normally take up extracellular, circulating FAs from dietary fats whereas lipid biosynthesis is usually restricted to hepatocytes, adipose tissue and mammary glands [ 43 , 44 ]. Cancer cells and specifically CRC cells were shown to change their source of lipids on the one hand by increasing extracellular uptake and on the other hand by reactivating de novo fatty acid synthesis regardless of extracellular lipid availability, providing them with metabolic flexibility and alternative sources of energy [ 12 , 42 , 45 ]. One source for scavenging extracellular lipids is adipocyte or hepatocyte-derived, plasma albumin-bound free-fatty acids.…”
Section: Lipid Biology In Crcmentioning
confidence: 99%
See 1 more Smart Citation